ANALISIS THEORY OF REASONED ACTION SERTA PENGARUH PRICE, LOCATION DAN DEVELOPER’S REPUTATION TERHADAP PURCHASE INTENTION PADA APARTEMEN DI SIDOARJO - Mega Meilya Alif (Jurnal Bisnis dan Keuangan, 2021)
The purpose of this study is to analyze the theory of reasoned action and the influences of price, location and developer’s reputation toward apartment purchase intention in Sidoarjo. This research uses a quantitative approach and include as clausal study. The sampling technique is non probability sampling. The criteria of the respondents are people who were born between 1980-2000 or the age group of 20-40 years in 2020 (millennials), who is planning to buy an apartment within the one year; and has never bought an apartment in Sidoarjo before. The techniques of data collection uses a survey method by five-level of Likert scale. The questionnaire was distributed by electronic links using email and social media. This study uses multiple linear regression assisted with the Statistical Program for Social Science (SPSS) software for the data analysis. The result of the study are attitude, subjective norms, price, location, and developer’s reputation have a significance influence toward purchase intention.